All creatures great and small - Herriot, James (St. Martin's Griffin, 2014)
The stories of a young veterinarian making his way in the rugged English countryside?and of the people and animals he met along the way? In the rolling dales of Yorkshire, a simple, rural region of northern England, a young veterinarian from Sunderland joins a new practice. A stranger in a strange land, he must quickly learn the odd dialect and humorous ways of the locals, master outdated equipment, and do his best to mend, treat, and heal pets and livestock alike.? This witty and heartwarming collection, based on the author's own experiences, became an international success, spawning sequels and winning over animal lovers everywhere. Perhaps better than any other writer, James Herriot reveals the ties that bind us to the creatures in our lives.